AIDS-Related Mycoses: Updated Progress and Future Priorities (2020)
Serious fungal infections continue to devastate people living with HIV and remain a leading cause of infection-related deaths in this population, second only to tuberculosis. The third AIDS-related mycoses workshop updated progress in the field over the last 3 years and highlighted six key action points for the future. © 2020